2008
DOI: 10.1038/nature06635
|View full text |Cite|
|
Sign up to set email alerts
|

A photosynthetic alveolate closely related to apicomplexan parasites

Abstract: Many parasitic Apicomplexa, such as Plasmodium falciparum, contain an unpigmented chloroplast remnant termed the apicoplast, which is a target for malaria treatment. However, no close relative of apicomplexans with a functional photosynthetic plastid has yet been described. Here we describe a newly cultured organism that has ultrastructural features typical for alveolates, is phylogenetically related to apicomplexans, and contains a photosynthetic plastid. The plastid is surrounded by four membranes, is pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
383
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 426 publications
(404 citation statements)
references
References 27 publications
19
383
1
1
Order By: Relevance
“…Recent evidence suggests that apicomplexans evolved from a free-living photosynthetic ancestor (1). This ancestry is reflected in the presence of a chloroplast-like organelle, the apicoplast (2).…”
mentioning
confidence: 99%
“…Recent evidence suggests that apicomplexans evolved from a free-living photosynthetic ancestor (1). This ancestry is reflected in the presence of a chloroplast-like organelle, the apicoplast (2).…”
mentioning
confidence: 99%
“…Nearly a decade ago, Moore et al (2008) first reported the isolation of an apicomplexan alga, Chromera veliae , from corals. This free-living photosynthetic alga lies on the evolutionary path to non-photosythetic apicomplexans such as the malaria pathogen and is therefore a bridge between photosynthetic phytoplankton, such as the dinoflagellate Symbiodinium , and non-photosynthetic, parasitic apicoplexans.…”
Section: The Specific Ecological Roles Of Scleractinian Corals On Cormentioning
confidence: 99%
“…This emergence is also influenced by light intensity, salinity, and nutrient levels (28,30). In an initial ultrastructural analysis of C. velia, internal, non-membranebound axonemes were noted (26). By analogy to its malariacausing relative Plasmodium, it was proposed that C. velia assembles its axoneme completely within the cytoplasm, most likely via an IFT-independent mechanism (26,28).…”
mentioning
confidence: 99%
“…C. velia is a photosynthetic microalga that was isolated from Australian hard corals and shows a range of genetic and morphological similarities to Apicomplexa (26)(27)(28). The life cycle of C. velia alternates between nonflagellate coccoid cells and motile biflagellate cells (26,28,29). The two flagella emerge from the anterior end of the cell, with the shorter (anterior) flagellum located to the anterior part of the longer (posterior) flagellum.…”
mentioning
confidence: 99%
See 1 more Smart Citation